Analisis Kapasitas Seismik Struktur Gedung Kantor Dinas KetahananPangan Provinsi Sumatra Barat - Thasbih Al Fajri; Rafki Imani; Zakpar Siregar (Jurnal Teknologi, 2020)
The office building of the food security office of West Sumatra Province is a multi-storey building with reinforced concrete structures built in earthquake-prone areas that have the potential for large-scale earthquakes such as the one that occurred in 2009. Based on USGS data, from December 2004 to October 2009 There have been 10 earthquakes measuring more than 5 on the Richter scale that rocked Indonesia and resulted in damage to buildings, both minor damage to heavy damage and evencollapsing. The big earthquake that occurred on September 30, 2009 in Padang City, West Sumatra, was measuring 7.6 on the Richter scale. In this study, evaluated the seismic capacity of a reinforced concrete building 4 (four) floors built in earthquake-prone areas in the city of Padang. The seismic capacity of the building is evaluated based on the standard published by Japan, namely The Standard for Seismic Evaluation of Existin Reinforced Concrete Building, 2001. In this evaluation, it only looks at the structural elements of the column on the first floor. Seismic capacity is expressed in terms of the lateral strength index and the ductility index of the building. The results of the evaluation of seismic capacity obtained the total strength index value of the building is 0.707. The seismic capacity of this building can be shown to be adequate or strongin earthquake-prone areas compared to the seismic capacity of reinforced concrete buildings that survived the massive earthquake of 7.6 on the Richter Scale in West Sumatra in September 2009. From the evaluation results on this building which is located in an area including the prone to strong earthquakes can be stated to be able to behave ductile and able to withstand an earthquake or not experience sudden collapse